Portföy yönetimi ve performansa göre ücretlendirme - Akbulut , Orhan Gazi (My University, 1999)
PORTFOLIO MANAGEMENT AND AWARD THE PRIZE ACCORDING TO THE PERFORMANCE Stock markets are the only places in the world where funds with reasonable prices are available and can be used efficiently and as a result of this be highly profitable. Capital markets is a new concept in our country has showed a fast growth and has become one of the leading markets among the developing markets . Companies that have joined the stock market have been able to provide themselves funds with almost no cost and have been able to add to their investments and growth. Contrary to this people who have invested their savings in the stock market have not been as profitable. This has been a result of poor analysis of the market and not being enough familiar to stocks. This has lead to creating new specialized fields in this market like portfolio management and consultants for investors. Specialization in these new fields need good education, high knowledge and experiance. But because of the sudden growth in the capital markets and the high demand from the investors, many people have started monaging portfolios and causulting investors without having enough experience and/ or knowledge about the rules of this market. As a natural result of this especially during crises there have been big losses in the number of investors. On the other hand professionally handled portfolios and specialized consultants have made their investors happy. This study is of five sections. Section 1 : Basic concepts for capital markets description of investors, and the tendency for risk. Section 2 : The kind of sawing changing the sawing to an investment and the risks involved during this change (process). Section 3 : The basic principles of the analysis and management of portfolios. The strategies to be applied while evaluating and revising portfolios. Section 4 : Evaluation methods of portfolios for higher income (profit). Also how these methods effect the success of a portfolio. Section 5 : As a result of a well managed portfolio managers and how to pay them. In 1986, with then beginning of the stock market, companies have been able to find funds with almost no cost and investors have been given new choices for investing their savings. There have been imported changes in the new investment alternatives and in the financial markets. These new investments that consist of movable values have been more profitable compored to the other altarnative investments but have also been riskier. This risk has either made them leave the stock market or has them go to specialists who know the market better. Naturally the result has lead to portfolio management and consultants for investors. Because analiyzing the level of risk knowing when and how much to buy needs specialization. In order to have portfolio management there must be confidince in the market. This confidence should be common portfolio manager and the investor and also between the investor and the market. There may be a relationship between the portfolio manager and the investor based on confidence but this all alone is not enough. The investor may have left uneasy if there is not enough confidence in how the market works. That is why the confidance for both portfolio manager and the market must be very strong and for this to happen the infrastructure must be built. Along whit a permanent confidance between the portfolio manager and the investor the market will function in a healtly and more efficient way. This will lead to bringing in foreign capital which is very important for developing countries. The reason of capital that has increased lately in the developing countries is that the investors have become different kinds. The different kinds of investors are confirming funds institutional investors. The person who trades movable value according to the performance. As known having alternative investments help lowering the risks and prevent big losses when there are unexpected events that effect the markets. Although the effect of foreign capital in developing countries is not 100 % predictable it has known that it has such effects as lowering the nominal and real interest rates and creates healthier functioning stock market having the stocks become higher in value, and also increases the prices of assets. Besides short term capital flow has the following positive effects in developing countries: - Some stocks become international. - Controling and organizing mechanisms work better. - Investors are secured. - Payments and exchanges become more efficient. - Accounting systems and balance declaration standards conformity with those that have been accepted in the international finance markets. Liberalization in the financial markets have lead to changes in the interes rates foreign currency rates and movable value rates and that is why portfolio management has become more important. All the changes in these markets effect one another and to be able to predict the results need good knowledge experience and specialization. How change in the foreign currency rates will effect the interest rates or how a treasury bond would be announcement of inflation rates would effect the market are all to be predicted and the portfolios should be revised. This production revison in the portfolios will have effect on the success of that portfolio manager. Nobody has the capability of changing the market conditions in their own favor. Only those who are able to predict the effects and are able to take the necessary steps (decissions) would be having a high perfonmance in portfilo management. High perfonmance in portfolio managament needs good analysis that would beat the market. To beat the market and to buy the right stock needs basic analysis. The timing for when to buy and when to sell needs techical analysis. It will not be by chance for a good portfolio managament who can tell the effects of the changes in the markets and can make the right analysis. When a portfolio manager is creating a portfolio : - Time (period) to hold the portfolio. - Choice of stocks and the ratio of alternative investments witkin the portfolio. - Necessary arrangements in the portfolio. - How to evaluate the portfolio and perfonmance. Should all be considered and set beforehand. Success in portfolio management needs to bare some costs. These costs for a good technical analysis are devices like telephones,faxes which enable fast information. A better prediction than the others needs correct and update information and good tecnicues to be used for healthy predictions. There are many efforts in this field in the world. Especially for beating the market studies on kantitatif models are done. Kantitatif modelsare in two groups depending on the methods of predicting. The first one is timing analysis which is to predict the future value of the socks. The second one is to the differentiation analysis which is to predict the value direction of the stock. No matter how sophisticated the analysis methods are when we take into consideration the effect of the movements in a market it is more important to be faster in the analysis and to use the results objectively to be successful in portfolio management and to reach a higher perfonmance. Buying the stocks that have been decided by using the analysis methods at the right time and making the correct evaluations in the movements of the market will reinforce the success of a portfolio manager. As the importance of portfolio management increases it is most important to evaluate the success of portfolio managers and to award them accordingly in order to increase their motivation which will also have positive impact on portfolio managament. This award will be the amount of payment made in relation with the perfonmance of that portfolio manager. This new concept will in a way take the portfolio manager a partner to that portfolio and will be given a share from the profit. This will increase the motivation and will lead to taking better care of the portfolios. If there is no profit in the portfolio, the portfolio manager will be getting a standard salary and will show more effort in order to compete with the other portfolio managers for a better income. Portfolio management and consulting investments in the Turkish capital markets are fields that are highly needed. The need for consulting investors is parallel with the growth of the finance markets. As a result of the increase of the peoples income and the developments in the finance markets there is need for qualified people in both consulting investments and in portfolio management. The need of such specialists both specialized and experienced in companies and faundations for portfolio management and consulting investments is felt more and more each day. Efforts for reducing this need will be helping in having a healthy and strong market and people will not be hesitating in bring their savings and investing in to these capital markets.
Keywords: Ekonomi; Finansman ekonomisi; Portföy yönetimi; Yatırım